A human right to healthy animals - Yeates, James William (Frontiers in Animal Science, 2024)
The United Nations has recognised a universal human right to a clean, healthy and sustainable environment. This right should include the right to healthy animals within that environment because (a) logically animals are part of the environment and (b) poor animal health can affect human health through mechanisms such as pathogen transfer, ecosystem damage, unsustainable resource utilisation and greenhouse gas emissions. Current definitions of health, and identified risk factors for animal and human health include physical, mental and social factors. This simple logic might be challenged from perspectives of (1) humans waiving their own right to health; (2) purported conflicting priorities, and (3) concerns that animals also have rights, but these challenges do not refute the underlying argument that the human right to a clean, healthy and sustainable environment includes a right to healthy animals.